WALKING PROPELLERS OF TRANSPORTATION VEHICLE FOR DRIVING UNDER STEPPE ROAD-OFF CONDITIONS - Asemkhanuly, Asylkhan (Journal of Applied Engineering Science, 2020)
Vast steppes of Kazakhstan mainly consist of  stubble and sandy loam soils, as well as salt marshes with solid surface. Therefore, it is possible to drive on them on conventional vehicles with pneumatic wheels. Where the land is developed for grain crops, the surface of the soil is soft, and where fodder crop rotations are cultivated, the surface of the soil is  as solid as stubble.Wherever land is used for economic needs, wheeled cars, tractors and agricultural machinery drive there. Unfortunately, they deteriorate a lot..   Service lifetime of trucks and cars in off-road conditions compared with service lifetime of them in urban environments is reduced by almost four times.Tractor trucks, tractor cultivators and all types of self-moving wheeled agricultural machinery are annually subjected to seasonal repairs as a result of  agricultural harvesting. Moreover, their maintenance is expensive.Accordingly, we cannot say that all goes well, but this happens unwillingly. What shall we do if there are no other types of progressive machinery? Mechanicians rush to answer the question if there is a need to introduce something new. They say - "What else could you ask for? All machines work. ” In fact, according to scientific forecasting, the design of these machines are supposed to be completely different in off-road conditions. Relief irregularities of soil supporting surface affect outrigger wheels with round cover disk strongly. In such cases not only a lot of energy is expended, but all the components and assemblies of undercarriage undergo vibrations, which causes severe wear to occur.
Keywords: Walking propellers, Transportation, Vehicle, Steppe road-off conditions